MAKLUMAT INDUSTRI DAN SAINS INFORMATION SERVICE FOR COMMERCE & INDUSTRY - Perpustakaan, Hamzah Sendut (Perpustakaan Universiti Sains Malaysia, 2006)
MALAYSIA PLANS TO DEVELOP GHS Malaysia hopes to implement the chemical hazard classification and communication system based on the Globally Harmonised System (GHS) by year-end. GSH, a system to define and classify hazards through a uniform hazard information on labels and safety data sheet to be used in worldwide communication, will be implemented in four sectors -- industrial workplace, agriculture, transport and consumer products. The international structure for harmonizing classification and labeling systems for chemicals will have a beneficial impact on chemical trade, the exchange of information related to chemicals, the cost of risk assessment and management of chemicals and ultimately the protection of workers, the general public and the environment. A plan to implement the GHS was adopted at the 2002 UN World Summit on Sustainable Development, held in Johannesburg, South Africa. Countries were encouraged to have the GHS fully operational by 2008. Sources were quoted.